ART THERAPY SEBAGAI ART-BASED ASSESSMENT PADA ANAK OPPOSITIONAL DEFIANT DISORDER (ODD) DI PANTI ASUHAN X DAN Y - Desti Apryanggun; Monty P Satiadarma; Debora Basaria (Universitas Bunda Mulia, 2018)
This study uses art therapy as an art-based assessment in children with ODD in orphanages. Art therapy is one form of therapy that also has an assessment function, especially as a projection test tool. Art therapy can be used as an assessment tools by using art media called art based assessment. The purpose of this study to determine the characteristics of children with ODD in orphanages through the use of art therapy as an art based assessment. The image analyze is based on colors, themes, styles of expression and composition. The study was conducted in August – November 2017. The results showed that five subjects used dominant colors is hot color and dark; theme a form of aggression; style of expression in drawing is well-controlled line but disorganized; and the combination of many images in middle position. Art therapy as an art-based assessment in this study is reliable because its accordance with the principle of reability such as repetitions theme, repetitions forms, and repetitions color. There is a matching result with the final diagnosis of children with ODD. Art-based assessment can be used as a consideration for assessing children with ODD to determine the appropriate treatment in children. Keywords: Art Therapy, Art Based Assessment, ODD, Orphanage